2021
DOI: 10.1097/jom.0000000000002314
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Ability of the Full and Short Versions of the Orebro Questionnaire for Absenteeism and Presenteeism Over the Subsequent 12 Months, in a Cohort of Young Community-Based Adult Workers

Abstract: Objective: The primary purpose of this study was to investigate the predictive ability of the Örebro Musculoskeletal Pain Screening Questionnaire (ÖMPSQ) in regard to work productivity (absenteeism and presenteeism) in early adulthood. Methods: A prospective study was performed using data from the Raine Study Generation 2 (Gen2) 22-year follow-up. The ÖMPSQ was completed at baseline, and absenteeism and presenteeism assessed at four intervals over the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
0
1
Order By: Relevance
“…Overall, the present results supplement the existing literature that has associated higher ÖMPSQ-SF scores (high-risk group) with the accumulation of self-reported sick leave days over a 1-year follow-up, 19 poorer return to work within 3 months, 37 and prolonged recovery from MSK and soft tissue injuries leading to generally later return to work. 21 , 38 In an Australian 1-year follow-up study, 39 the ÖMPSQ-SF demonstrated poor discrimination in terms of work absenteeism and presenteeism, but this difference to our findings may originate from the different age groups we studied (young adults vs. middle-aged individuals) and outcome data collection methods (self-reports vs. registry-based). Importantly, in this study, we also clearly showed that not only the high-risk group but also the medium-risk group had a higher registry-based number of sick leave days and likelihood of disability pension.…”
Section: Discussioncontrasting
confidence: 82%
“…Overall, the present results supplement the existing literature that has associated higher ÖMPSQ-SF scores (high-risk group) with the accumulation of self-reported sick leave days over a 1-year follow-up, 19 poorer return to work within 3 months, 37 and prolonged recovery from MSK and soft tissue injuries leading to generally later return to work. 21 , 38 In an Australian 1-year follow-up study, 39 the ÖMPSQ-SF demonstrated poor discrimination in terms of work absenteeism and presenteeism, but this difference to our findings may originate from the different age groups we studied (young adults vs. middle-aged individuals) and outcome data collection methods (self-reports vs. registry-based). Importantly, in this study, we also clearly showed that not only the high-risk group but also the medium-risk group had a higher registry-based number of sick leave days and likelihood of disability pension.…”
Section: Discussioncontrasting
confidence: 82%